SPATIO-TEMPORAL PATTERNS AND ENVIRONMENTAL IMPACT OF INDUSTRIAL AGGLOMERATION IN THE LAGOS REGION, NIGERIA (2014)
Studies on industrial agglomeration have focused on the advantages of geographical proximity and increasing returns to scale of production. These studies have largely neglected other fundamental aspects, especially the spatio-temporal dynamics of agglomeration and the perceived environmental impact. This study, therefore, examined the clustering of firms over time and the perceived effects of the clustering on the environment in the Lagos region, between 2005 and 2009. A survey of industrial estates and firms was carried out. The Manufacturers Association of Nigeria Industrial Directory, and Lagos State Ministry of Commerce and Industry records were used to determine the location of firms. A structured questionnaire was used to collect data on the characteristics and clustering patterns of the existing 103 firms in the twelve industrial estates. Data on the perceived severity of environmental impact of agglomeration were obtained through a questionnaire survey administered to 120 heads of households in a spatial systematic sampling procedure. The head of the household nearest to each of the estates was first sampled. Thereafter, heads of household located at intervals of 10 houses were interviewed. The ANOVA was used to determine the variation in the pattern of agglomeration economies over time. Canonical Correlation was used to determine the relationship between the structural characteristics of firms and agglomeration economies. Pearson Product Moment Correlation was employed to determine the relationship between distance from an industrial estate and the perceived severity of environmental impact. The analyses were done at p< 0.05%. Agglomeration varied from 23.0% in Ikeja to 1.9% in Ogba industrial estates. This variation may be explained by the age and available facilities in these industrial estates. The relationship between the structural characteristics of firms and agglomeration economies is significant (F-cal = 3.52). Agglomeration economies varied significantly among the firms (F-cal = 34.92). Access to financial institutions, accounted for 33.1% in 2005; 47.6% in 2006; 47.2% in 2007; 45.7% in 2008 and 51.5% in 2009. Telecommunications in contrasts accounted for 4.9% in 2005; 1.9% in 2006; 1.9% in 2007; and 0.0% in 2008 and 2009 respectively. The wood and wood products industry group benefitted the most; in 2005 (31.8%); 2006 (22.8%); 2007 (42.7%); 2008 (38.5%); and 2009 (61.4%) compared to the chemical and pharmaceutical industry group which benefitted the least: 5.2% in 2005; 8.6% in 2006; 7.9% in 2007; 9.5% in 2008; 15.6% in 2009. Air (20%) and noise pollution (20.0%) were perceived by the residents as the most significant environmental impact of agglomeration. About 48.0% respondents indicated that the environmental problems were severe. The severity reflected a distance decay function (R = -0.641). Seventy-five per cent of the respondents indicated that firms were not doing enough to address the identified negative impacts. Agglomeration varied among the industrial estates as well as amongst the industry groups. Air and noise pollution were perceived as the most significant environmental problem associated. Agglomeration should therefore be encouraged to promote industrial development, while the negative impact should be curtailed.